2021
DOI: 10.18280/ijht.390312
|View full text |Cite
|
Sign up to set email alerts
|

An Individual Household-Based Heating Metering and Charging Management System for Central Heating in Community Residential Buildings

Abstract: The optimization of heating metering method in the heating season has very important and practical value for energy saving and emission reduction, however, existing studies haven’t comprehensively analyzed the heating metering and charging management systems adopted by residential buildings with adjustable heat supply, and the problem of fair heat sharing hasn’t been well solved yet. To fill in this research gap, this paper designed an individual household-based heating metering and charging management system.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In the study, a pricing management system has been designed to ensure that the heating measurement is fair in the mass housing building and to solve the heat-sharing problem. He found that this measurement system is important in terms of energy optimization, energy saving, and emission values [15]. Cho et al (2020) investigated the effect of hydraulic balancing of the heating system in buildings on energy saving and improving the thermal conditions of the volume.…”
Section: Wwwdergiparkgovtr/tdfdmentioning
confidence: 99%
“…In the study, a pricing management system has been designed to ensure that the heating measurement is fair in the mass housing building and to solve the heat-sharing problem. He found that this measurement system is important in terms of energy optimization, energy saving, and emission values [15]. Cho et al (2020) investigated the effect of hydraulic balancing of the heating system in buildings on energy saving and improving the thermal conditions of the volume.…”
Section: Wwwdergiparkgovtr/tdfdmentioning
confidence: 99%
“…When there are a large number of households in a building, it is unfortunate that there is often a lack of detailed specifications or installation instructions to guide the installation locations. Therefore, the monitoring devices are always installed randomly, and the average value of these randomly installed monitoring points was calculated and used to evaluate the heating requirement of a building, a heating station, or a heating system [16]. However, the household's temperature was not only affected by the supplied heating but also by the location, the occupancy rate, etc.…”
Section: Introductionmentioning
confidence: 99%